I-JOB: Job Search Platform for Internships Placement - Anuar, Nur Syazwani (IRC, 2020)
Internships are work, and curriculum-based educational experiences evolved through the collaboration between educators and employers. Internships aim to give students real-world experience allowing them to transcribe classroom knowledge into practice (Carmella et al., 2020). All universities in Malaysia require students to undergo internships as a pre-requisite for them to graduate. Companies will also receive job appeals from students to carry out practical at their companies. An internship program for every university may differ from one another in terms of duration and year of study the students will go for internships. This dissertation is written for the development of a job search platform to find an internship placement. The project aims to help students to find an internship placement where companies can directly offer the job with a full job description to the students and students can apply the offer through the website. In addition, the company can also find applicants if they need an intern. There are two phases of the methodology used which are by conducting preliminary studies and system development. Literature review of the project and interview the stakeholders will be done to carry out the primary tasks. This project will be using the Waterfall Methodology for system development.